Marissa the science fairy - Meadows, Daisy (London : Orchard Books, 2016)
Rachel and Kirsty can't wait to go to school together for a week! But trouble starts when Jack Frost steals Marissa the Science Fairy's magical star badge. Can the girls get it back?
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction